2020
DOI: 10.1093/nar/gkaa662
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of hippuristanol-resistant mutants reveals eIF4A1 dependencies within mRNA 5′ leader regions

Abstract: Hippuristanol (Hipp) is a natural product that selectively inhibits protein synthesis by targeting eukaryotic initiation factor (eIF) 4A, a DEAD-box RNA helicase required for ribosome recruitment to mRNA templates. Hipp binds to the carboxyl-terminal domain of eIF4A, locks it in a closed conformation, and inhibits its RNA binding. The dependencies of mRNAs for eIF4A during initiation is contingent on the degree of secondary structure within their 5′ leader region. Interest in targeting eIF4A therapeutically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
(76 reference statements)
1
21
1
Order By: Relevance
“…The precise step-by-step mechanism leading to these changes, however, remains to be fully elucidated. DMDAPatA and hippuristanol, which have different mechanisms of eIF4A inhibition compared to rocaglates ( Naineni et al, 2021 ; Shen and Pelletier, 2020 ; Steinberger et al, 2020 ), replicated at least some key reprogramming effects. Hippuristanol inhibits the interaction of both free and eIF4F-bound eIF4A with RNA ( Bordeleau et al, 2006b ), while pateamine is more similar to the rocaglates, increasing the target’s interaction with RNA, making it less available to take part in the complex ( Bordeleau et al, 2006a ).…”
Section: Discussionmentioning
confidence: 91%
“…The precise step-by-step mechanism leading to these changes, however, remains to be fully elucidated. DMDAPatA and hippuristanol, which have different mechanisms of eIF4A inhibition compared to rocaglates ( Naineni et al, 2021 ; Shen and Pelletier, 2020 ; Steinberger et al, 2020 ), replicated at least some key reprogramming effects. Hippuristanol inhibits the interaction of both free and eIF4F-bound eIF4A with RNA ( Bordeleau et al, 2006b ), while pateamine is more similar to the rocaglates, increasing the target’s interaction with RNA, making it less available to take part in the complex ( Bordeleau et al, 2006a ).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that the natural marine product, elatol, inhibits eIF4A1, providing a highly promising target for cancer therapy (Peters et al, 2018). Furthermore, hippuristanol, silvestrol, pateamine A, and oxo-aglaiastatin all target eIF4A1 (Itoua Maïga et al, 2019;Naineni et al, 2020;Steinberger et al, 2020). Rocaglates have been shown to possess potent antineoplastic activity both in vivo and in vitro by enhancing mRNA binding to both eIF4A1 and eIF4A2 (Chu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hippuristanol, as a polyoxygenated steroid, selectively inhibits eIF4A through binding to its C-terminal domain [ 119 ]. Hippuristanol suppresses the RNA-binding activity of eIF4A by locking eIF4A in a closed conformation, but does not prevent its ATP-binding activity ( Table 2 ) [ 72 , 120 ].…”
Section: Development Of Rna Helicase Inhibitors For Clinical Treatmentmentioning
confidence: 99%